How the West was sung : music in the Westerns of John Ford - Kalinak, Kathryn Marie, 1952- (University of California Press, 2007)
Provides a comprehensive analysis of Ford's use of music in his iconic westerns. Covering a variety of critical approaches and incorporating original archival research, this book explores the director's oft-noted predilection for American folk song, hymnody, and period music. It states that Ford used music as more than a stylistic gesture.